An Australian State-Based Cohort Study of Autoimmune Encephalitis Cases Detailing Clinical Presentation, Investigation Results, and Response to Therapy - Swayne, Andrew; Warren, Nicola; Prain, Kerri; Gillis, David; O'Gorman, Cullen; Tsang, Benjamin K-T.; Muller, Claire; Broadley, Simon; Adam, Robert J.; McCombe, Pamela; Wong, Richard C.; Blum, Stefan (Frontiers in Neurology, 2021)
Introduction: Autoimmune encephalitis is a disorder associated with antibodies directed against central nervous system proteins with variable clinical features. This study aims to add to knowledge of the disease by reporting the details of a cohort of patients with autoimmune encephalitis in Queensland, Australia. Methodology: We surveyed patients with autoimmune encephalitis diagnosed and managed through public hospitals in Queensland, Australia between 2010 and the end of 2019. Cases were identified via case detection through a centralised diagnostic neuroimmunology laboratory (Division of Immunology, HSQ Pathology Queensland Central Laboratory, Brisbane, Queensland, Australia) and a survey of neurologists. Data including demographic details, clinical presentation, investigation results, treatments including immune therapy and outcomes was collected. Results: Sixty cases of antibody positive autoimmune encephalitis were identified. Twenty-eight were of anti-NMDA-receptor encephalitis with other cases associated with antibodies against LGi1, Caspr2, glycine receptor, DPPX, GABAB receptor, IgLON5, GFAP and SOX1. The number of diagnosed cases, especially of anti-NMDA-receptor encephalitis has markedly increased over the period 2017 to 2019. Clinical presentations were marked by heterogeneous symptom complexes and prolonged hospital admissions. Imaging studies were largely normal or non-specific. There was a response to immune therapy and a low mortality rate. Most cases affected by this disorder were left with ongoing symptoms associated with mild disability. Conclusion: Autoimmune encephalitis in Queensland, Australia is an increasingly common but complex clinical entity marked by heterogoneous presentations, response to immune therapy and outcome results marked by low mortality and incomplete recovery.